The effect of atmosphere on the flash-sintering of nanoscale titania ceramics. (1st July 2021) - Wang, Qizhong; Watts, Connor S.; Athanasiou, Christos E.; Dai, Zhenghong; Hu, Mingyu; Sheldon, Brian W.; Padture, Nitin P.
Abstract: Flash-sintering is a promising approach for the ultra-rapid densification of ceramics at low furnace temperatures under an applied electric field. Here we have studied the effect of atmosphere on the flash-sintering of titania (TiO2 ) nanopowders under an applied electric field of 400 V.cm −1, and find a dramatic reduction in the flash-onset furnace temperature ( T F ), from 648°C in air to 239°C in argon (Ar). The reduced T F is close to the TiO2 Debye-temperature limit. This is attributed to a combination of nanocrystalline nature of the TiO2 powder and the O2 -lean Ar atmosphere, resulting in enhanced electrical-conductivity characteristics. The reduced T F also results in finer, uniform average grain sizes (360 nm to 190 nm) and lower, uniform porosity (0.5% to 1.4%), going from the anode to the cathode. In contrast, in air the corresponding average-grain-size range is 9.6 μm to 1.3 μm and the porosity range is 1.9% to 3.3%. Graphical abstract: Image, graphical abstract